Varietas Unggul Padi Tahan Hawar Daun Bakteri: Perakitan dan Penyebaran di Sentra Produksi - Rina Hapsari; Untung Susanto; Satoto Satoto (Puslitbang Tanaman Pangan, 2016)
Bacterial leaf blight or BLB (Xanthomnas oryzae pv. oryzae or Xoo) is one of the main diseases in riceproducing countries, including Indonesia. Development of resistant varieties is an effective approach to be done in endemic areas of BLB. Breeding program for bacterial leaf blight resistant varieties could be effective by utilizing bioassay technique screening, selection in endemic areas, and MAS technique. The resistant varieties to be grown in some regions should have considered the composition of Xoo. Several resistant varieties have been released and those varieties can be recommended for endemic areas of BLB with a specific composition.